The Management of Iron Chelation Therapy: Preliminary Data from a National Registry of Thalassaemic Patients. (5th June 2011) - Ceci, Adriana; Mangiarini, Laura; Felisi, Mariagrazia; Bartoloni, Franco; Ciancio, Angela; Capra, Marcello; D'Ascola, Domenico; Cianciulli, Paolo; Filosa, Aldo
Abstract : Thalassaemia and other haemoglobinopathies constitute an important health problem in Mediterranean countries, placing a tremendous emotional, psychological, and economic burden on their National Health systems. The development of new chelators in the most recent years had a major impact on the treatment of thalassaemia and on the quality of life of thalassaemic patients. A new initiative was promoted by the Italian Ministry of Health, establishing a Registry for thalassaemic patients to serve as a tool for the development of cost-effective diagnostic and therapeutic approaches and for the definition of guidelines supporting the most appropriate management of the iron-chelating therapy and a correct use of the available iron-chelating agents. This study represents the analysis of the preliminary data collected for the evaluation of current status of the iron chelation practice in the Italian thalassaemic population and describes how therapeutic interventions can widely differ in the different patients' age groups.